Providing a Model for Overcoming Job Burnout in Imam Khomeini Relief Committee - Hatamikiya, Darab; Amirnejad, Ghanbar; Ahmadi, Seyyed Ali Akbar; Daniali Deh Houz, Mahmood (Future of Work and Digital Management Journal, 2025)
The present study was conducted based on the paradigm of pragmatism and followed an inductive–deductive approach. To achieve the research objective, an exploratory mixed-method design (qualitative–quantitative) was employed. In terms of purpose, this study is an applied–developmental research that seeks to explain and propose a model for overcoming job burnout in the Imam Khomeini Relief Committee. Based on the data collection method, this is a non-experimental (descriptive) study conducted through a cross-sectional survey. The qualitative study population consisted of senior managers and experienced human resource personnel of the Imam Khomeini Relief Committee. Purposeful sampling was used, and theoretical saturation was achieved with 15 participants. The quantitative study population consisted of managers and experts of the Imam Khomeini Relief Committee, estimated at 150 individuals based on effect size and test power, and selected using a simple random sampling method. Data were collected using semi-structured interviews and a researcher-made questionnaire. For analyzing the expert interviews, thematic analysis and Maxqda software were used, and the questionnaire data were analyzed using the partial least squares (PLS) method with SmartPLS software. The research findings showed that managerial factors, structural factors, and cultural factors affect the empowerment of the target community and the improvement and development of human resources. Job enrichment, career development, and compensation and rewards also influence the management of clients’ expectations and the enhancement of digital responsiveness to them. At the next level of the model, these components affect stress management and conflict management. Ultimately, by the influence of the previous-level components on employees’ job motivation and organizational intimacy, overcoming job burnout is achieved.